2010
DOI: 10.1242/jcs.066266
|View full text |Cite
|
Sign up to set email alerts
|

The Lyn kinase C-lobe mediates Golgi export of Lyn through conformation-dependent ACSL3 association

Abstract: The Src-family tyrosine kinase Lyn has a role in signal transduction at the cytoplasmic face of the plasma membrane upon extracellular ligand stimulation. After synthesis in the cytoplasm, Lyn accumulates on the Golgi and is subsequently transported to the plasma membrane. However, the mechanism of Lyn trafficking remains elusive. We show here that the C-lobe of the Lyn kinase domain is associated with long-chain acyl-CoA synthetase 3 (ACSL3) on the Golgi in a manner that is dependent on Lyn conformation but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…ACSL3 also interacts with the Src-family tyrosine kinase Lyn in the Golgi of HeLa and COS-1 cells and allows Lyn to be transported to the plasma membrane (149). Because a mutant of ACSL3 that lacks the AMP/ATP-binding motif can still function for Lyn transport, it was concluded that ACSL activity was not required for this role, however, enzyme activity was not measured (149).…”
Section: Long-chain Acyl-coa Synthetasesmentioning
confidence: 99%
See 1 more Smart Citation
“…ACSL3 also interacts with the Src-family tyrosine kinase Lyn in the Golgi of HeLa and COS-1 cells and allows Lyn to be transported to the plasma membrane (149). Because a mutant of ACSL3 that lacks the AMP/ATP-binding motif can still function for Lyn transport, it was concluded that ACSL activity was not required for this role, however, enzyme activity was not measured (149).…”
Section: Long-chain Acyl-coa Synthetasesmentioning
confidence: 99%
“…Because a mutant of ACSL3 that lacks the AMP/ATP-binding motif can still function for Lyn transport, it was concluded that ACSL activity was not required for this role, however, enzyme activity was not measured (149). Although mammalian synthesis of 4 and 16-carbon acyl-CoAs for protein acylation have not been described, in Xenopus, triacsin C-mediated inhibition of ACSL activity blocks the palmitoylation of Gα (197).…”
Section: Long-chain Acyl-coa Synthetasesmentioning
confidence: 99%
“…Immunofluorescence staining was performed as described112955. In brief, cells were fixed with 4% paraformaldehyde in phosphate-buffered saline (PBS) for 20 min, and permeabilized with 0.2% Triton X-100 in PBS for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…To detect tyrosine phosphorylation of proteins, cell lysates were prepared with SDS-sample buffer containing 10 mM sodium orthovanadate, 20 mM ß-glycerophosphate, and 50 mM NaF. Immunodetection was performed by enhanced chemiluminescence and examined using an image analyzer ChemiDoc XRSplus (Bio-Rad) as reported previously1150. Sequential reprobing of membranes with various antibodies was performed after the removal of antibodies from the membranes or inactivation of HRP by 0.1% NaN 3 , according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation